How many cores should be taken from each region of interest when performing a targeted transrectal prostate biopsy? - Serhat Cetin; Arif Huseyinli; Murat Yavuz Koparal; Ender Cem Bulut; Murat Ucar; Ipek I. Gonul; Sinan Sozen (Prostate International, 2023)
Background: The number of core biopsies required per region of interest (ROI) is controversial, as is the localization of the core to be taken from a lesion. This study aimed to determine the ideal biopsy core number and location in a multiparametric magnetic resonance imaging guided targeted prostate biopsy (TPB), without reducing the clinically significant prostate cancer (csPC) detection rate. Materials and methods: Data of patients who had PI-RADS ≥3 lesions on multiparametric magnetic resonance imaging and underwent a TPB in our clinic between October 2020 and January 2022 were reviewed, retrospectively. The first and second cores were taken from the central part of the ROI, whereas the third and fourth cores were taken from the right and left peripheries of the ROI. We compared the csPC detection success of single-, 2-, 3-, and 4-core samplings. Results: Software-based transrectal TPB was performed on 251 ROIs in a total of 167 patients. Internal Society of Urological Pathology Grade Group ≥2 cancer was detected in at least one core in 64 (25.4%) lesions. Moreover, csPC was detected in 42 (65.6%) ROIs in first-core biopsies; in 59 (92.2%) ROIs in first- and second-core biopsies; in 62 (96.9%) ROIs in first-, second-, and third-core biopsies; and in 64 (100%) ROIs in first-, second-, third-, and fourth-core biopsies. Using McNemar's test for comparison, a significant difference was found in terms of csPC detection success between performing first-core and second-core biopsies (65.6 – 92.2%, p < 0.001); by contrast, no significant difference was observed in csPC detection success between 2-core and 3-core biopsies (92.2% - 96.9%, p = 0.24). Furthermore, no significant difference existed between performing second-core and fourth-core biopsies in terms of csPC detection success (92.2%–100%, p = 0.07). Conclusion: We concluded that taking 2-core biopsies from the center of each ROIs during a transrectal TPB is sufficient for diagnosing csPC.